Digital photography complete course - Taylor, David, 1969 April 13-; Hallett, Tracy; Lowe, Paul, 1963-; Sanders, Paul (Landscape photographer) (2015)
This book helps you to build your photography skills week-by-week. The Digital Photography Complete Course is the perfect one-on-one learning programme for any aspiring photographer. This modular 20-week course guides you through every aspect of digital photography, using a combination of tutorials, step-by-step photo shoots, practical assignments and fun Q&As. Demystify digital photography and build your photography skills with comprehensive guides on everything you need to know, from conveying movement and using natural light, to understanding exposure and mastering composition. This book will help you to understand and use your camera to its full potential so that you don't just take good pictures - you take great ones.
Making your first photos -- Focusing -- Using shooting modes -- Getting the right exposure -- Achieving the right contrast -- Using depth of field -- Lenses -- Wide-angle lenses -- Telephoto lenses -- Taking close-up photos -- Conveying movement -- How to compose -- Compose like an expert -- Lessons in color -- the color of light -- Using natural light -- Working with flash -- Working in low light -- Black and white -- Working on a project.
Includes index.
Keywords: Photography -- Digital techniques